2021
DOI: 10.1186/s12890-021-01565-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood and tooth element status in asthma cases: a preliminary case–control study

Abstract: Background Asthma is a common respiratory disorder; some data were present on the correlation between increased levels of trace elements and the risk of asthma development. It was aimed to evaluate the levels of 13 selected blood and tooth elements (magnesium, phosphorus, calcium, chromium, manganese, iron, copper, zinc, strontium, molybdenum, cadmium, lead, mercury) in a well-controlled asthma group and the control group. Methods During the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Endogenous reactive oxygen species [ROS], as well as free radicals, which are important in the development of asthma, were created by inflammatory cells an harm tissues. [ 3 ], The lung's antioxidant defence systems against block these harmful oxidants [ 27 ]. The most important antioxidant systems are the superoxide dismutase (SOD) which contains zinc and copper in their structures, and hence zinc is essential for the optimal functions of immune system [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous reactive oxygen species [ROS], as well as free radicals, which are important in the development of asthma, were created by inflammatory cells an harm tissues. [ 3 ], The lung's antioxidant defence systems against block these harmful oxidants [ 27 ]. The most important antioxidant systems are the superoxide dismutase (SOD) which contains zinc and copper in their structures, and hence zinc is essential for the optimal functions of immune system [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Ge Yang et al, 2019, high blood cadmium levels were substantially linked to asthma patients [ 76 ]. According to research by S. Songül et al, non-smokers' lung function may be adversely affected by exposure to greater concentrations of heavy metals, especially cadmium [ 77 ]. In our study, serum concertation of Cd was statistically significant higher in asthma patient males, asthmatic obese patient males and obese patient males when compared to controls males and in Pearson corelation analysis, Cd is negatively corelated with TAS in asthma patient males and in asthmatic obese females showed Cd is negatively corelated with systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catherine et al observed a positive relationship between serum Cu and abdominal obesity. Furthermore, the risk of elevated TGs was decreased with ascending tertiles of Cu [ 62 ]. However, there were no associations between serum Cu and TG levels among children and adolescents in the NHANES 2011–2014 study [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on the association between zinc and asthma incidence. Some studies supported the contributory role of zinc in asthma prevention [ 10 19 ], whereas others failed to support this claim [ 20 26 ]. The association between zinc and asthma hence remains an open question.…”
Section: Introductionmentioning
confidence: 99%